Air velocity and temperature distribution in culverts - Tommik, Karina; Knutsson, Sven; Laue, Jan; Lintzén, Nina (Cold Regions Science and Technology, 2023)
Uneven frost heave in roads and railways is a frequent problem in cold regions leading to degradation of structures. To improve drainage, culverts are frequently integrated into road and railway embankments. The presence of culverts changes the temperature distribution in the surrounding soil as cold air passes through the culvert. Consequently, frost depth and corresponding frost heave are increased in the vicinity of the culvert compared to the rest of the structure if frost susceptible soil is present. For an accurate frost related design, information of heat balance between the culvert and the surrounding soil is needed. A field study focusing on convective heat transfer in culverts was conducted in northern Sweden by the authors. Temperatures and air velocities in culverts of three sizes (0.6, 0.8 and 3.4 m) were recorded. Analysis of obtained data is presented in this paper with emphasis on the influence of air velocity on the temperature distribution. Influence of wind on development of airflow in culverts is also addressed. Accuracy of trained gaussian process regression (GPR) models is estimated in predicting temperature distribution inside of culverts. It is concluded, based on the field measurement data, that airflow can significantly affect temperature distribution inside culverts and development of airflow in culverts is largely influenced by the orientation of the culvert in relation to the predominant wind direction. Validerad;2023;Nivå 2;2023-06-02 (hanlid)